Routine Coagulation Tests in Patients With Nonvalvular Atrial Fibrillation Under Dabigatran and Rivaroxaban Therapy: An Affordable and Reliable Strategy?. (5th March 2019) - Silva, Vanessa M.; Scanavacca, Maurício; Darrieux, Francisco; Cavalheiro, Cyrillo; Strunz, Celia C.
Dabigatran and rivaroxaban, direct oral anticoagulants (DOACs), affect coagulation tests, and knowledge of their effects is important for therapeutic monitoring. Our aim was to examine the association between DOAC levels and routine coagulation tests in patients with nonvalvular atrial fibrillation. Samples from patients receiving dabigatran (150 mg) and patients receiving rivaroxaban (20 mg) were collected 2 hours after drug intake. Direct oral anticoagulant concentrations were determined using direct Hemoclot thrombin inhibitor (HTI) assay (HTI test) and a direct Xa inhibitor (Anti Xa-Riva). The routine coagulation measured included activated partial thromboplastin time (aPTT) and prothrombin time (PT). The median plasmatic dabigatran was 128.3 ng/mL (95% confidence interval [CI]: 93.7-222.6 ng/mL). The HTI exhibited a good correlation with aPTT ( R 2 = 0.74; P < .0001). The median plasmatic rivaroxaban was 223.9 ng/mL (95% CI: 212.3-238.9 ng/mL). Anti-Xa-Riva correlated with PT ( R 2 = 0.69, P < .0001) and aPTT (R 2 = 0.36, P < .001), but prolonged PT results were obtained, even below the rivaroxaban therapeutic range (20%). The routine coagulation tests were able to identify out of therapeutic range concentrations for dabigatran and rivaroxaban. We suggest the use of these screening tests to better understand and monitor the subtherapeutic concentrations of these DOACs.